Struggling for land access: The success and failure of social movement actors' framing strategies in conflicts over large-scale land transformations - Louisa Prause (Freie Universität Berlin, Junior Research Group 'Global Change - Local Conflicts' (GLOCON), 2016)
Struggles over meaning construction are an essential part of conflicts over large-scale land transformations. To advance the land access claims of local communities, social movement actors engage in specific framing strategies to mobilize resources and support. This article explores how the discursive context shapes the success or failure of social movement actors' framing strategies in conflicts over large-scale mining and agro-industrial projects. Discursive opportunity structures (DOS) and framing are the key theoretical concepts used. I argue that the outcomes of framing strategies can only be understood when we combine DOS with a thorough analysis of social movement actors' ability to act on the opportunities provided by discursive structures. Empirically, the study compares conflicts over gold mining and agro-industry in Senegal. Some elements of the discursive structures differ depending on the purpose of the large-scale land trans for ma tion in question and as such provide distinct opportunities for social movement actors. Other elements of the discursive structure are tied to large-scale land transformations in general. As the empirical analysis shows, not all social movement actors can use these opportunities in the same way. The article contributes to our understanding of the importance of discourses and framing strategies in conflicts over large-scale land transformations. Conceptually, I explore the strengths and weaknesses of a theoretical framework combining DOS and framing. – – Konflikte um großflächige Landtransformationen zugunsten von Bergbau und Agrarindustrie haben in den letzten Jahren stark zugenommen. Dieser Artikel untersucht die diskursive Dimension dieser Konflikte. Im Zentrum steht die Frage nach dem Erfolg oder Misserfolg von framing Strategien sozialer Bewegungsakteure. Ob framing Strategien erfolgreich sind oder nicht lässt sich einerseits anhand von diskursiven Gelegenheitsstrukturen (DOS) erklären. Andererseits beeinflussen die Konstruktion ihrer Zukunftsvisionen und Fähigkeiten unterschiedlicher Bewegungsakteure, sowie ihrer Gegenspieler_innen, inwiefern Bewegungsakteure sich mit ihren Forderungen durchsetzen können. Empirisch wird ein Konflikt um eine Goldmine mit einem Konflikt um ein agrarindustrielles Projekt im Senegal verglichen. Dieser Vergleich zeigt, dass DOS un terschiedlich ausgestaltet sind, abhängig vom Zweck der Inwertsetzung von Land, also für Bergbau oder Agrarindustrie. Gleichzeitig gibt es Gemeinsamkeiten in den Diskursen, in Bezug auf die Abwägung von sozialen und ökologischen Risiken. Diese übergreifende Struktur der Diskurse kann jedoch von unterschiedlichen Akteuren nicht gleichermaßen genutzt werden. Der Artikel leistet einen Beitrag zum Verständnis der Bedeutung von Diskursen und framing Strategien in Konflikten um großflächige Landtransformationen. Gleichzeitig werden Stärken und Schwächen eines theoretischen Rahmens aufgezeigt, der DOS und framing kombiniert.
Keywords: 330; Social movements; conflicts; land grabbing; mining; discursive opportunity structures; framing; Soziale Bewegungen; Konflikte; land grabbing; Bergbau; diskursive Opportunitätsstrukturen; Framing